2021
DOI: 10.3390/nano11061399
|View full text |Cite
|
Sign up to set email alerts
|

Photodehydrogenation of Ethanol over Cu2O/TiO2 Heterostructures

Abstract: The photodehydrogenation of ethanol is a sustainable and potentially cost-effective strategy to produce hydrogen and acetaldehyde from renewable resources. The optimization of this process requires the use of highly active, stable and selective photocatalytic materials based on abundant elements and the proper adjustment of the reaction conditions, including temperature. In this work, Cu2O-TiO2 type-II heterojunctions with different Cu2O amounts are obtained by a one-pot hydrothermal method. The structural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The total time of a photocatalytic test was 180 min. The photoreactor works thus under static conditions, which differs from the dynamic conditions used by other researchers where a continuous flow of ethanol vapors (mixed with water vapors) was employed via bubbling [ 18 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total time of a photocatalytic test was 180 min. The photoreactor works thus under static conditions, which differs from the dynamic conditions used by other researchers where a continuous flow of ethanol vapors (mixed with water vapors) was employed via bubbling [ 18 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, it has been found that TiO 2 shows a high photocatalytic efficiency in the decomposition of pollutant substances such as dye wastewater [ 8 11 ], soiling [ 12 ], and harmful organic materials [ 13 15 ]. Also, TiO 2 powders show promising results for the decomposition of ethanol in various environments [ 16 18 ]. Moreover, investigations have shown the possibility for applying TiO 2 in hydrogen production by water decomposition [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In photocatalysis, the Z-scheme heterojunction catalysts had excellent properties which were not found in ordinary photocatalysts and common type II catalysts [49][50][51]. The Z-scheme heterojunction greatly improved the redox property and electron transport rate of the catalyst by generating effective electron-hole recombination within the two semiconductors [52].…”
Section: Introductionmentioning
confidence: 99%
“…ZIP-67 was chosen because Co is in the structure, and consequent Co oxide-based catalysts have potentially high applicability to water splitting reactions [ 28 ]. Cu and Ti were chosen because they have been extensively used as substituent materials and catalyst supports in photocatalysis and electrocatalysis [ 28 , 29 , 30 , 31 , 32 ]. Therefore, the present results provide a useful strategy for the design of new catalyst materials with high efficiency for energy and environment fields via CO 2 reduction and water splitting.…”
Section: Introductionmentioning
confidence: 99%